2020
DOI: 10.18203/issn.2454-2156.intjscirep20202076
|View full text |Cite
|
Sign up to set email alerts
|

Common invisible symptoms of multiple sclerosis

Abstract: <p class="abstract">Multiple sclerosis (MS) with its protean manifestations of central and peripheral nervous system pose a challenge to its management in different clinical scenario. The issue becomes much more complicated with occurrence of strange and unusual symptoms intermingling with common symptoms in people living with MS. The frequency and severity of these unusual symptoms changes overtime and raise a suspicion of other neurological disease. The occurrence of any of these symptoms at times may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Symptoms of MS can affect the physical, cognitive, and emotional status of patients [ 4 6 ]. The most common physical symptoms reported in the literature include pain, fatigue, tingling sensation, weak bladder control, visual problems, vocal changes, difficulty breathing, muscle weakness, weak bones, and gastrointestinal dysfunction [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of MS can affect the physical, cognitive, and emotional status of patients [ 4 6 ]. The most common physical symptoms reported in the literature include pain, fatigue, tingling sensation, weak bladder control, visual problems, vocal changes, difficulty breathing, muscle weakness, weak bones, and gastrointestinal dysfunction [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some symptoms *Corresponding author: Rami Masa'Deh, Applied Science Private University, Amman, Jordan. E-mail: r_masadeh@asu.edu.jo; Phone: +962 79 6067657 Submitted: 30 March 2021/Accepted: 01 October 2021 DOI: https://doi.org/10.17532/jhsci.2021.1229 commonly include pain, sensory problems, visual disturbances, elimination dysfunction, impaired mobility, mood changes, cognitive changes, and fatigue (8,9). Studies have shown that the very common symptom of fatigue -defined as an individual perception of deficiency in the physical or mental energy which affect the daily activities (10) -is particularly significant in its impacts on the activities of daily living of individuals diagnosed with MS (11,12).…”
Section: Introductionmentioning
confidence: 99%